2021
DOI: 10.3390/pharmaceutics13070923
|View full text |Cite
|
Sign up to set email alerts
|

Histological Studies on a Newly Isolated Bacillus subtilis D10 Protease in the Debridement of Burn Wound Eschars Using Mouse Model

Abstract: Background: Proteases are among the most important industrial enzymes, playing a critical role in the physiological, biochemical, and regulatory processes of all living organisms. This study evaluated the histological effects of a Bacillus subtilis D10 protease in combination with the antibacterial ointment silver sulfadiazine (SSD) on the burned skin of mice. Materials and Methods: The bacterial proteolytic enzyme was produced and purified through DEAE-Sepharose CL-6B and Sephadex G-100 FF. The in vitro prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The use of them as detergent additives represent the largest application among the industrial enzymes. Another industrial process that has received attention is the enzyme aided dehairing of animal hides and skin in the leather industry (Al-Dhuayan et al, 2021). The goal of this study was to clone the local Bacillus subtilis D9 alkaline protease gene in the yeast system for high expression level of D9 alkaline protease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of them as detergent additives represent the largest application among the industrial enzymes. Another industrial process that has received attention is the enzyme aided dehairing of animal hides and skin in the leather industry (Al-Dhuayan et al, 2021). The goal of this study was to clone the local Bacillus subtilis D9 alkaline protease gene in the yeast system for high expression level of D9 alkaline protease.…”
Section: Discussionmentioning
confidence: 99%
“…Different reports have focused on the characterization and applications of alkaline proteases produced by B. subtilis group, recovered from Saudi Arabia, because of their industrial importance in feather degradation, wound healing, and detergents (Al-Dhuayan et al, 2021;Mahmoud et al, 2021;Almahasheer et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in accordance with several studies reported in the literature. Such studies showed that the inflammatory phase restores homeostasis, and that, in the proliferative phase, fibroblasts and other cells from the connective tissue infiltrate the wound site and secrete cytokines, attracting keratinocytes and leading to re-epithelialization [26,46]. Preventing prolonged inflammation by suppressing the production of inflammatory cytokines is a desirable target for wound healing products; excessive inflammation results in chronic wounds and scar formation [47].…”
Section: Discussionmentioning
confidence: 99%
“…are mostly the microbial source to generate the proteases. Bacillus -derived alkaline proteases have numerous applications in industry, including organic synthesis, food, pharmacology, leather, and bioremediation ( Tarhriz et al., 2014 ; Al-Dhuayan et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%